A Re-Vision of To Kill a Mockingbird and Roll of Thunder, Hear My Cry - Michelle M. Falter (University of Oklahoma Libraries, 2015)
In this paper the author argues for a "re-visioning" of two young adult literature texts by examine the ways in which race is constructed/deconstructed within To Kill a Mockingbird and Roll of Thunder, Hear My Cry. The piece begins by examining how the books are perceived in mass culture, then leads into an analysis of how race is (de)constructed through key scenes related to family, history and land ownership. By examining the two pieces of literature in tandem, differing ideologies become apparent. Implications for the teaching of these texts in light of these ideologies, the selective tradition, and authenticity in the selection of multicultural texts conclude this piece.